Tuning the Coercive Field by Controlling the Magnetization Reversal Process in Permalloy Modulated Nanowires - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2020)
Magnetic nanowires of diameter d with a concentric cylindrical modulation of larger diameter D can lead to the production of devices with a variety of coercive fields. Besides D, the modulation thickness t and its position z along the axis of the wire are varied in the vicinity of values usually reported in the experimental literature. It is shown that the system can be understood as the combination of a long wire (with its usual properties for large aspect ratios), a short wire with lower coercive field and a wider modulation with a tendency to produce an early vortex configuration that softens the whole system from the magnetic point of view. The triggering mechanism to achieve the reversal at different coercive fields is studied by means of snapshots of the configurations just prior to the reversal itself. Altogether, upon spanning the parameter space (D,t, and z) a variety of hysteresis curves are obtained and a large range of coercive fields are shown to be possible. Micromagnetic simulations by means of Mumax3 solving the Landau-Lifshitz-Gilbert equation provide the theoretical framework of this work. Possible extensions of this work are also mentioned. © 2020 Elsevier B.V.